The Role of Native-Language Knowledge in the Perception of Casual Speech in a Second Language - Mitterer, Holger; Tuinman, Annelie (Frontiers in Psychology, 2012)
Casual speech processes, such as /t/-reduction, make word recognition harder. Additionally, word-recognition is also harder in a second language (L2). Combining these challenges, we investigated whether L2 learners have recourse to knowledge from their native language (L1) when dealing with casual-speech processes in their L2. In three experiments, production and perception of /t/-reduction was investigated. An initial production experiment showed that /t/-reduction occurred in both languages and patterned similarly in proper nouns but differed when /t/ was a verbal inflection. Two perception experiments compared the performance of German learners of Dutch with that of native speakers for nouns and verbs. Mirroring the production patterns, German learners' performance strongly resembled that of native Dutch listeners when the reduced /t/ was part of a word stem, but deviated where /t/ was a verbal inflection. These results suggest that a casual speech process in a second language is problematic for learners when the process is not known from the leaner's native language, similar to what has been observed for phoneme contrasts.